Toxin Neutralization Efficacy of Catechin and Silymarin against Anthrax Toxins - Taskeen, Shumaila; B Rawool, Deepak; Aggarwal, Somya; Somani, Vikas; Bhatnagar, Rakesh (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present study investigated the in-vitro toxin neutralization potential of FDA-approved polyphenols; catechin and silymarin against anthrax lethal and edema toxin. The titration of protective antigen (PA) against a fixed concentration of LF, and EF induced a linear dose-dependent cytotoxic effect with maximum attainable cytotoxicity at 10 μg/mL PA, and 1 μg/mL LF/EF in RAW264.7 and CHO.K1 cells. The LT and ET-induced cytotoxicity were assessed using MTT assay, and cAMP ELISA, respectively. All the tested concentrations (100, 10, 1, 0.1 μM) of catechin and silymarin exhibited a highly significant and dose-dependent reduction in LT-induced cytotoxicity (p<0.01). Further, a highly significant reduction in cAMP levels in ET-intoxicated cells was observed for the higher concentrations of both compounds (p<0.01), except at 0.1 μM concentration, while the mean cAMP levels at 100, and 10 μM of silymarin were less as compared to that at similar concentrations of catechin, the difference was insignificant (p>0.05). The study emphasized the anti-toxin potential of catechin and silymarin, which could augment the antimicrobials in anthrax infection. Further, future studies focused on their pharmacodynamics, kinetics, and determination of clinically safe therapeutic doses in vivo are warranted.